How volatile are African food prices? - Minot, Nicholas (International Food Policy Research Institute, 2013)
Instability in the price of staple foods is an important source of risk in developing countries. This is particularly true in Africa south of the Sahara because of the low incomes of many African households. Poor urban households allocate a large share of their income to food, so food price volatility affects their purchasing power. Many poor rural households depend on agriculture for their livelihood, so they too are directly influenced by food price volatility.